Anchorage Capacity of Headed Reinforced Bars in Concrete - Sachdeva, Payal (My University, 2022)
In reinforced cement concrete (RCC) structures, the bond between the concrete and the steel bar is critical. When the member geometry is insufficient for the full development of straight bars, headed bars can be used to anchor reinforcing steel due to the shorter development lengths and compact size, they can reduce congestion in the beam-column joints. Fiber- reinforced cementitious composites have been increasingly used in recent years on beam- column joints and the introduction of headed bars is a practical solution to eliminate the congestion problem caused by hooked bars in beam-column joints. The key in this study is the headed reinforced bar, which is used to anchor the steel in the concrete instead of straight or hooked bars. There has been very little research on the behavior of headed bars in RCC structures, especially when they are used with high-strength concrete. The ASTM A970 and ACI 318-19 codes are used to design and manufacture headed bars. The design provisions of ACI 318-19 limit the yield strength of headed bars to 413.68 MPa and concrete compressive strength to 41.6 MPa due to the limited research performed on headed bars to date. The main parameters in this study are concrete compressive strength, steel bar diameter, percentage of steel fibers, and head shape. The influence of head shapes (Square, Circular, and Rectangular), concrete compressive strength (M20, M40, and M60), the diameter of steel bar (16, 20, and 25 mm), and steel fibers (0, 0.5, 1, and 1.5%) on the anchorage capacity of headed bars have been evaluated. The behavior of headed bars in concrete is investigated through 324 pullout tests, embedded concentrically at depth of eight times the bar diameter in the cylindrical specimens having size 150 X 300 mm. Additionally, the International Federation for Structural Concrete (fib) provides the code MC2010 for advanced design methods for concrete structures and the application of improved structural materials, and EN 1992-1-1 gives a general basis for the design of structures in plain and reinforced concrete. Therefore, the comparison analysis of bond stress for all the specimens have been made using these three codes as mentioned above. Also, the bearing capacity of concrete has been calculated and compared with the pullout capacity of the headed bars. Two failure modes namely, steel and concrete-blowout have been observed and the prevailing mode of failure is steel failure. Based on load-deflection curves 6 and derived descriptive equations, it is observed that the circular headed bars have displayed the highest peak load. The present study also emphasizes the evaluation of the performance of steel fiber reinforced concrete (SFRC) external beam-column joints (BCJ) using headed bars as an anchorage mechanism and the comparison has been made with the conventional bars which have been detailed in accordance with ACI 318-19 and ACI 352R-02. The repository of previous BCJ work has been further expanded by researching the effect of structural parameters i.e. compressive strength (M20 and M40) and steel fibers (1 and 1.5%) on the hysteresis curve, ductility, stiffness, energy dissipation, and cracking on all specimens. The experimental results have revealed that the conventional bars can be significantly replaced by the headed bars for the areas vulnerable to earthquakes due to their higher load carrying capacity with better ductility and stiffness response and reducing congestion in BCJ. The anchorage strength of headed bars has been determined using the test results of beam-column joint specimens. A numerical model for improving the anchorage capacity of headed bars has also been proposed using non-linear regression analysis through dummy variables. Results have revealed that the anchorage capacity of headed bars increases with the increase in concrete compressive strength, the diameter of steel bar, and steel fibers, which have been validated by non-linear regression analysis using dummy variables. The developed equations using non-linear regression analysis have been compared to test results from previous studies to come up with new development length design criteria. Genetic programming has been used to create a model that predicts the maximum load-carrying capacity of headed bars when subjected to direct pull-out load in this research. The GP model is based on a large and reliable database containing 324 test specimens and four variables that control the load-carrying capacity of headed bars: concrete compressive strength, bar diameter, bar embedment depth, and percentage of steel fibers. In comparison to the peak load equation developed using regression analysis, the proposed model using GP provides the most accurate peak load prediction and is the most fitting to the experimental database. Also, the bond strength equation for the headed bars has been predicted using regression analysis and has been compared to the bond strength formula given by ACI 318-19, in which two main factors i.e., 7 compressive strength of concrete and percentage of steel fibers are missing. After analyzing the bond strength, it has been determined that the bond strength has been improved by adding compressive strength and steel fiber factors. Thus, these two factors should be included in the ACI 318-19 code.
Keywords: Anchorage capacity; Headed Bars; Steel Fibers; Pull out test; Beam Column joint